Narrowing of knee joint space in patients with pseudogout. Issue 1 (February 1981) - Ellman, M H; Brown, N L; Levin, B
Abstract : Abnormalities of joint space in knee roentgenograms were compared among 28 symptomatic patients with pseudogout and 2 control groups consisting of spouses of patients and hospital based patients with knee pain. Joint space narrowing was significantly more frequent in the pseudogout patients than in the 2 control groups. Division of patients and controls into 3 age groups revealed a striking degree of joint space narrowing in the youngest patients with pseudogout. Our study suggests that symptomatic patients with pseudogout have joint destruction beginning at a relatively early age. We speculated that this may reflect concurrence of chondrocalcinosis and another disease such as osteoarthritis.